2004
DOI: 10.1039/b411882k
|View full text |Cite
|
Sign up to set email alerts
|

Water splitting with silver chloride photoanodes and amorphous silicon solar cells

Abstract: A thin silver chloride layer deposited on a conducting support photocatalyzes the oxidation of water to O(2) in the presence of a small excess of silver ions in solution. The light sensitivity in the visible part of the spectrum is due to self-sensitization caused by reduced silver species. Anodic polarization reoxidizes the reduced silver species. To test its water splitting capability, AgCl photoanodes as well as gold colloid modified AgCl photoanodes were combined with an amorphous silicon solar cell. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 90 publications
(19 reference statements)
0
29
0
1
Order By: Relevance
“…/ AgCl/Ag n photoanode and the amorphous Si solar cell led to photoelectrochemical water splitting to O 2 and H 2 ; see Fig. 10 (left) [74]. In other yet preliminary experiments we prepared zeolite monolayers on conducting surfaces like gold coated glass and gold foil [75].…”
Section: Photocatalytic and Photoelectrochemical Water Splittingmentioning
confidence: 97%
“…/ AgCl/Ag n photoanode and the amorphous Si solar cell led to photoelectrochemical water splitting to O 2 and H 2 ; see Fig. 10 (left) [74]. In other yet preliminary experiments we prepared zeolite monolayers on conducting surfaces like gold coated glass and gold foil [75].…”
Section: Photocatalytic and Photoelectrochemical Water Splittingmentioning
confidence: 97%
“…1,2 It also has photocatalytic activities that are useful for water splitting and decomposition of organic pollutants. [3][4][5][6] It has been demonstrated that decoration of AgCl with Ag nanoparticles can greatly improve the light absorption property and photostability of the AgCl nanoparticles. [7][8][9] In addition, AgCl can be used in fabricating antiseptic catheters, bone cements, and fabrics owing to its antibacterial property.…”
Section: Introductionmentioning
confidence: 99%
“…To allow sufficient ionic transport when no separators are present, often highly acidic or basic electrolytes are used (Seger and Kamat, 2009;Chen Q. et al, 2013;Currao et al, 2004). These have the disadvantage of being corrosive and expensive which makes them difficult to apply on a large scale as highly resistant reactor materials must be used throughout the system.…”
Section: Design Of Practical Small To Large Scale Pec Cellsmentioning
confidence: 99%